Perianal Paget's disease. Issue 626 (December 1977) - Lock, M. R.; Katz, D. R.; Parks, A.; Thomson, J. P.
Abstract : Paget's disease involves the ducts of apocrine glands and the overlying epidermis and is considered to be locally neoplastic. It is capable of developing into invasive carcinoma and in this event the prognosis is poor. The perianal skin may be affected by Paget's disease. This is a rare disorder and the four patients who have been seen with this disease at St Mark's Hospital since 1930 are described.